2014
DOI: 10.3109/09638288.2014.956813
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-reported disability after performance-based tests in obese and non-obese individuals diagnosed with osteoarthritis of the knee

Abstract: Obese individuals with knee OA may over-estimate their ability to perform physical activities, and may under-estimate their level of disability compared to non-obese individuals with knee OA. In addition, self-reported physical activity seems to be a strong indicator of disability in individuals with knee OA, particularly for individuals with a sedentary life style. Implications for Rehabilitation Osteoarthritis is a progressive joint disabling condition that restricts physical function and participation in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…In the present study, older adults were selected from the census records based on risk factors, while in the study of Op het Veld and colleagues older adults were recruited from different settings such as clients of a physical therapy practice, people admitted to a hospital, and people attending daycare facilities [ 15 ]. A previous study, for example, showed that self-reported levels of disability were higher after the completion of performance-based tests [ 25 ]. One can assume that participants undergoing physical therapy will experience physical limitations in real time and be aware of it.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, older adults were selected from the census records based on risk factors, while in the study of Op het Veld and colleagues older adults were recruited from different settings such as clients of a physical therapy practice, people admitted to a hospital, and people attending daycare facilities [ 15 ]. A previous study, for example, showed that self-reported levels of disability were higher after the completion of performance-based tests [ 25 ]. One can assume that participants undergoing physical therapy will experience physical limitations in real time and be aware of it.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 studies have investigated whether habitual physical activity levels predict pain responses to acute exercise in individuals with chronic pain. Coriolano et al 21 found that people with knee osteoarthritis who self-reported more physical activity experienced less exacerbation in pain after completing performance-based tests and a physiological test (submaximal arm ergometer test). In people with fibromyalgia, Umeda et al 187 showed that participants who were more physically active reported a smaller increase in ratings of muscle pain intensity during isometric handgrip exercise.…”
Section: Pain Outcomes After Acute and Regular Exercise In Individmentioning
confidence: 99%
“…Self-report questionnaires of pain-related disability, rather than only pain scores, are more likely to provide an accurate illustration of a patient's level of ability at the time of assessment. 216 Many obese patients are inactive due to pain, which creates a vicious cycle. Accelerometry was effective in a study monitoring relationships among obesity, chronic pain, and mobility.…”
Section: Monitoring the Effect Of Chronic Pain And Obesity Treatmentmentioning
confidence: 99%